STUDI PERILAKU PETUGAS PARAMEDIS DAN CLEANING SERVICEDALAM PENGELOLAAN LIMBAH MEDIS PADAT 01 RSUD DR SOETOMO SURABAYA - Fransisca Fitri Novitasari; Sri Mardoyo; Sukiran Al Jauhari (GEMA LINGKUNGAN KESEHATAN, 2013)
RumahSakit Umum Daerah Dr. Soetomo, Surabaya as one of medical service means, isa place where both sick and healthy people are gathering together. Activities of RSUD Dr.Soetomo will produce solid and liquid medical waste thatmay affect ennironmental pollution andhealth disorder. The behavior of Paramedic and Cleaning Service personnel significantly affectin managing the solid medical waste management.This research is a descriptive one, namely a research method aimin to assess thebehavior of Paramedicand Cleaning Service personnel, comprising of knowledge level, attitude,and action in managing those solid medical wastes in Rumah Sakit Umum Daerah Dr. Soetomo,Surabaya. Population in this research was 298 Paramedic and Cleaning Service Personnel,spread in 13 wards, total sample was 75 Paramedic personnel and 3 Cleaning Servicepersonnel. Data obtained was further analyzed descriptively with table.The research result on solid medical waste management in Rumah Sakit Umum DaerahDr. Soetomo Surabaya, having satisfactorily knowledge level assessment each was 50,6% forParamedic personnel and 67% for Cleaning Service personnel. While for satisfactorily attitudeassement was 53,3% for Paramedic personnel and 100% for Cleaning Service personnel.Regarding satisfactorily performance assessment, it ,was achieved of 18,6% for Paramedicpersonnel, andO%for Cleaning Service personnel.Following the observation result of Paramedic and Cleaning Service personnel, it issuggested for their further guidance and briefing in behavior improvement regarding solidmedical waste management.Keywords : Behavior, Hospital